2016
DOI: 10.1088/1367-2630/18/10/105011
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced proton acceleration in an applied longitudinal magnetic field

Abstract: Using two-dimensional particle-in-cell simulations, we examine how an externally applied strong magnetic field impacts proton acceleration in laser-irradiated solid-density targets. We find that a kTlevel external magnetic field can sufficiently inhibit transverse transport of hot electrons in a flat laserirradiated target. While the electron heating by the laser remains mostly unaffected, the reduced electron transport during proton acceleration leads to an enhancement of maximum proton energies and the overa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 38 publications
(57 reference statements)
0
33
0
Order By: Relevance
“…In the case of the applied B-field (yellow curves) the electron spectrum is somewhat enhanced. It is worth noting that previous simulations with a much shorter laser pulse and a much shorter preplasma showed no significant impact on electron heating by an applied 1.5 kT B-field 11 . It remains to be determined using detailed electron tracking whether the changes in the electron spectra are caused by enhanced electron acceleration in the preplasma.…”
Section: A Enhanced Proton Acceleration From Solid Targetsmentioning
confidence: 72%
“…In the case of the applied B-field (yellow curves) the electron spectrum is somewhat enhanced. It is worth noting that previous simulations with a much shorter laser pulse and a much shorter preplasma showed no significant impact on electron heating by an applied 1.5 kT B-field 11 . It remains to be determined using detailed electron tracking whether the changes in the electron spectra are caused by enhanced electron acceleration in the preplasma.…”
Section: A Enhanced Proton Acceleration From Solid Targetsmentioning
confidence: 72%
“…We note that under realistic multidimensional conditions (i.e. with a finite laser focal spot), the intrinsic angular divergence of the hot electrons will cause them to expand transversely through the target, and thus become more and more diluted around the laser axis, where the fastest ions are driven 48 . In a target thin enough (d < ct pulse /2) that the sheath electric field does not undergo disruption events, this will mainly speed up the decay of the on-axis sheath field, reducing the maximum achievable proton energy.…”
Section: Discussionmentioning
confidence: 97%
“…In the context of the considered problem, such fields can indeed be considered 2 as static and uniform, thus justifying our approximation. It has already been shown that the fields of this magnitude can meaningfully impact relativistic laser-plasma interactions 44,46 , but their role on electron acceleration has not been examined, which strongly motivated this work. We note that, at a number of facilities, it would be possible to exploit the presence of both long and short pulse beamlines to simulataneously generate such strong quasi-static B-fields and examine their effect on the shortpulse interaction.…”
Section: Introductionmentioning
confidence: 99%